Prosjekt -98 i Granåsen K-120 - Braathen, S.; Ettema, G.
Review: This project was evolved in the process together with the project of making a new work-capabilities list, for modern ski jumping. In the time of this work FIS came up with a demand of having new profile for Granåsen Ski jump hill. A project involving measurements of flying path in the Granåsen hill was then quite suited. Both for finding the flying path of modern ski jumping, and make better arguments in the discussion of rebuilding the Granåsen hill. The project was maintained during autumn -98. The hill used for measurements was Granåsen K-120. Method: As seen in app. 1 it was set up five cameras around the hill. All calibrated from the shape of the hill. The hills exact profile was measured by the Department of Building and Construction Engineering, at NTNU(Norwegian University of Science and Technology, Trondheim). 18 jumpers did a total of 80 jumps over 2 days in the measurement. All jumps were made on watered porcelain in run track. Wind condition differentiated between 2 m/sec. tail wind, to 4,5 m/sec. head wind. There was big difference in anthropometrics and jumping technique in the group of jumpers. Jumpers were ranking from top 10 in the world (Norwegian national team), to rather poor local jumpers. 24 jumps were chosen qualified as measurement data. An overview of the results is shown in app. 3. A simulating tool was build up on an Excel worksheet based on the data from this flying path measurement. This simulating tool (called `simjump` from now), have the capabilities of showing the length of a jump, in a free chosen hill construction. It also has the possibility of manipulating with jumpers weight, velocity, size and direction of jumping impulse, friction coefficient between ski and snow and putting in a drag/lift component (see app. 2). The measurement data was put into the `simjump` tool, together with the new FIS profile proposal. Results: All the jumps measured had a straight part in the last half of the flying path. The angle between this straight and the horizontal was between 39° and 41°. The difference between Granåsen -98, and new FIS proposed profile are shown by the graph in app. 4, together with some chosen measured jumps, and one simulated jump on the first version of `simjump`. Because the graphs showed that the measured jumps and the mathematically simulated jump has an almost identical flying path in the first part of the flight, but a totally different flying path in the last part (see app. 5). The `simjump` tool got an upgrade. This upgrade made `simjump` possible to involve a certain angle, which made the simulated flying path change from a ballistic curve to a straight line (se app. 6). By inserting data in the new `simjump` for elder hill construction used in WC´s of ski jumping, the difficulties of deciding take-off velocity are shown. It gives to low height in the first part of flight, because of to steep outrun. This gives a wrong angle between the angle of the straight of the outrun and jumpers flying angle. Conclusions: The first conclusion is that the proposed change of profile in Granåsen K-120 is not worthwhile. In old style ski jumping, with a ballistic curve of the flying path from take-off to landing it was natural that the outrun had a straight line. But from this study we will conclude that the outrun of new hills should have a long curve from P point, which will meet the jumper flying on his straight line. And every part of the outrun should be less than 37° steep to the horizontal. But all hills that has a straight line of an angle less than 37,5°, should not necessarily being rebuild. At the same time, it is necessary to look at the flying capabilities of the jumpers. It is a clear positive thing to make the jumpers a little bit less effective flyers. This would cause less cost of rebuilding hills. And the flying path would be less influenced of changing wind. Less air consistent suit, and smaller skis should be natural consequences.